(untitled) (Journal of Informatics Education and Research, 2023)
The flipped classroom model has gained popularity in recent years as a way to enhance student learning outcomes. In this model, students watch pre-recorded lectures or complete online activities before class, and class time is devoted to discussion, group work, and problem-solving activities. This paper reviews the existing literature on the effectiveness of the flipped classroom model in enhancing student learning outcomes, including academic performance, engagement, and critical thinking. The findings suggest that the flipped classroom model can have a positive impact on student learning outcomes when it is implemented effectively. However, there are also challenges associated with the implementation of the flipped classroom model, such as the need for access to technology and the need for clear guidelines and support for both students and teachers.